ANALISIS BUTIR SOAL UJIAN AKHIR SEMESTER MATA KULIAH MAPEL SD MATEMATIKA I TAHUN AKADEMIK 2018/2019 - Wisnu Budi Wijaya, I Komang; Sri Darmayanti, Ni Wayan (Institut Hindu Dharma Negeri Denpasar, 2019)
The aim of this research was to analyze the questions item of final exam semester on Mapel SD Matematika 1 subject based on validity, reliability, difficulty index and potential differentiator. This research was descriptive. The population of this research was the student’s answer sheet on their final exam semester of Mapel SD Matematika 1 subject. The sampling technique use was saturation sampling. The data research was descriptive analyzed. The results of this research were : 1) Each question item of final exam semester of Mapel SD Matematika 1 subject had validity value between 0,300-0,700 and classified high, 2) Reliability value 0,897 and classified high, 3) Difficulty index of each question was on interval 0,300-0,700 and classified medium and 4) potential differentiator of question number 1 dan 3 were fair and number 2, 4 and 5 were good.